Jahrbuch für die Geschichte Mittel- und Ostdeutschlands (De Gruyter, 2009)
Comparative Prussian history constitutes the methodical focus of the Yearbook. Particular emphasis is placed on the areas east of the rivers Elbe and Saale: during the Middle Ages they produced those Eastern settlements to be merged into the Prussian state in the early modern age. Political and constitutional history, economic and social history, community history, and church, cultural and educational history are all taken into consideration.